Pelaksanaan Anggaran pada Dinas Prasarana Jalan Tata Ruang dan Permukiman Propinsi XXX - Sartika, Dewi; Nini, Nini (Jurnal Kajian Manajemen Bisnis, 2015)
This study aimed to analyze the mechanisms and procedures for implementing the budget of the Road Infrastructure, Spatial, and Settlement Office of XXX Province whether it is already in accordance with applicable regulations and analyzing factors that caused high realization of the budget on the second semester. This study is a descriptive analysis of the financial management and its activities is using qualitative and quantitative approaches. The data used in this study are primary data and secondary data and to obtain the research data used deep interview technique, documentation and observation.The results showed the mechanisms and budget execution procedures are not in accordance with the applicable rules and there are activities that is not on time from a predetermined schedule. The factors that caused high realization of the budget on the second semester is the delay of Budget Implementation Document (DPA) to the Department; slow separation of activities; the slow process of Executive Officer of Engineering Activity (PPTK) appointment; late tendering process; and Procurement Service Unit officers (ULP), which is doing dual task . The results of the study also shows the weakness of the Internal Control System (SPI) of the Road Infrastructure, Spatial, and Settlement Office in financial management and operations that caused volume and quality of work reduced. To optimizing and maximizing budget implementation, Road Infrastructure, Spatial, and Settlement Office has to improve its Internal Control System, has responsibility and higher authority on the job, perform separation of functions, and improve the integrity of management, review and do close monitoring of the work, both internal and external, in order to avoid irregularities and misappropriation of the budget implementation.